Assessing Natural Variation in Fruits and Seeds of Harar (Terminalia chebula Retz) - Thakur, Sanjeev; Sharma, Kamal; Gupta, Atul (Indian Journal of Agroforestry, 2020)
A survey of harar growing areas in district Sirmour of Himachal Pradesh and district Panchkula of Haryana, India was carried out to assess the natural variation occurring in fruits and seed characters and screen out the elite genotypes among the populations. The survey revealed problems faced by harar growers in production and marketing of fruit. Study showed significant variation in fruit size, weight and seed/pulp ratio. Fruit diameter showed significant and positive correlation with green fruit weight, the most important character from market point of view. The correlation revealed that selection for fruit diameter would also result in selection for fruit green weight. On the basis of fruit and seed characteristics, accession T11Â was found to be best followed by T12 and T14.